(untitled) (Nóema, 2013)
Why an emergentist account of subjectivity? On the one hand, emergentism provides a new paradigm to rethink subjectivity beyond any dualism. At the same time, the issue of subjectivity puts a strain on emergentism itself, and pushes it beyond its limits. To show it, in the present paper I address a fundamental question: How can we describe subjectivity from an emergentist perspective? To answer, I will tackle Samuel Alexander’s and Alfred North Whitehead’s emergentist accounts of subjectivity. Alexander locates subjectivity into a consistent emergentist framework, but his model of subjectivity remains grounded in the classical interpretation of subjectivity as mind. Whitehead gives a more innovative model of subjectivity, which implies a radical revision of its temporality and connection to the world, but this leads him beyond emergentism as a whole.